Gender differences in motivations to attend festivals in Saudi Arabia. Issue 2 (2nd December 2019) - Alshammari, Faten; Whaley, Jeremy; Hur, Songyee; Kim, Youn-Kyung
Abstract : Purpose: The purpose of this paper is to conduct a within-gender analysis and between-gender differences in seeking (personal and interpersonal) and escaping (personal and interpersonal) motivations to attend a non-traditional festival in Saudi Arabia. Specific objectives were: to conduct a within-gender analysis in motivations to attend a non-traditional festival in Saudi Arabia; and to examine between-gender differences in motivations to attend a non-traditional festival in Saudi Arabia. Design/methodology/approach: Based on the data collected from 458 attendees at a non-traditional festival in Saudi Arabia, the authors employed network analysis for within-gender analysis and MANOVA and ANOVA for between-gender comparison. The network analysis served two purposes, in that it examined each item's predictability for each gender, and analyzed the correlations among motivation items within each gender. In addition, the General Linear Model served to compare the male and female groups' motivations to attend the non-traditional festival. The authors first performed MANOVA for each dimension and then ANOVA for each dimension's individual items. Findings: Within-gender analysis reveals that several sets of motivations were associated strongly for both genders. This suggests that Saudi Arabians seem to enjoy entertainment because it projects the festival mood; they want to escape both from home and work and attend the festival to relieve stress by changing their routine pace. However, gender differences were apparent in several other items, especially for the group of women. Between-group comparison analysis shows significant gender differences in several elements of motivation. Overall, personal seeking and escaping were greater for males than females. In contrast, interpersonal seeking was greater for females than males. Research limitations/implications: Entertainment seems to be a key contributor to the festival mood because entertainment and the festival mood were related closely for both genders. In fact, personal and interpersonal escaping means were greater than personal interpersonal seeking means for both genders. Indeed, opportunities exist to develop non-traditional festivals in the country further. Gender differences were identified in several items of personal seeking and escaping, and interpersonal seeking. With respect to personal seeking, men tend to seek the entertainment, festival mood and the event's uniqueness more than do women, a finding that their higher means in personal escaping supported. It is clear that men view the festival as a way to enjoy themselves to escape from their jobs and daily stress to a greater degree than do their female counterparts. Women are more likely to seek interpersonal experiences in that they are more likely to enjoy the festival because it offers the opportunity to meet new people and spend quality time with family and friends. This study has several limitations, leading to suggestions for future research. Because seeking and escaping motivations have been used relatively little in the festival setting, future researchers should develop a valid scale of personal and interpersonal seeking and escaping motivations specifically for festivals employing both qualitative and quantitative methods. Second, while the data were collected at a single non-traditional festival, future research can use multiple sites to increase the ability to generalize the findings. Third, although this study was limited to Saudi Arabia, further research can apply seeking and escaping motivations, both at the personal and interpersonal levels, to other cultures to extend the applicability of the framework used in this study. Practical implications: Non-traditional festival managers need to focus on an atmosphere that provides festivities, as many people in the Saudi Arabian culture appear to be escaping from their everyday lives to enjoy themselves and with family and friends. To appeal to male workers, festival organizers and managers need to advertise and market the events' mood and liveliness overall with photos of workers leaving the office free of stress and looking forward to attending an event. To appeal to women who desire unique experiences that a variety of forms of entertainment provide, event managers must ensure that the entertainment is innovative and creative, and differs from what other festivals provide to attract more female attendees. Also, festival planners must focus on events that incorporate the family unit and promote the opportunity to meet new people to appeal to women in Saudi Arabia. Originality/value: This is the first study to examine gender differences in festival motivations in Saudi Arabia. The relaxation of the historically strict and conservative cultural values, coupled with the country's desire to develop its tourism and event sector, provides an ideal opportunity for future research. The authors hope that this research will stimulate further interest in the country with the goal to develop and market its tourism sector and products on the world's stage.